PERUBAHAN TINGKAT KECEMASAN ANAK YANG MENDAPAT IMUNISASI INJEKSI SETELAH DILAKUKAN PERMAINAN PRIMA - Sevia Kurnia Fitri; Nurul Pujiastuti; Lucia Retnowati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Children who are undergoing treatment after injection often experience problems, so that these conditions often cause feelings of anxiety in themselves and their families. The emergence of these feelings of anxiety can spur children to use negative and positive coping mechanisms in overcoming anxiety so that it affects child development. Efforts were made to reduce children's anxiety by providing a PRIMA game (Maze Game for Anxiety). The purpose of the study was to determine changes in the level of anxiety of children who were given immunization injections after being given the PRIMA game.Methods: The research method uses case studies. The technique of collecting data is a questionnaire using the MYPAS scale. Sampling using purposive sampling technique as many as 4 respondents.Results: The results showed that the subjects who were given the PRIMA game intervention experienced a decrease in the level of anxiety in the post test results. Meanwhile, those who were not given the intervention experienced an increase in anxiety.Conclusion: It is hoped that health workers and parents can use this PRIMA game to reduce anxiety in children after injection, especially during the DPT booster I immunization. Further research can be carried out on more respondents and evaluated before and after giving the PRIMA game.